Al-Ma'tsurat therapy to increase the gratitude of mothers who accompany children in distance learning - Wasudin, Wasudin; Mumtaza, Shabrina Nur; Muthoharoh, Inayatul; Abidah, Thifal Ufairoh; Hyoscyamina, Darosy Endah (Journal of Research and Measurement in Psychology: JPPP, 2022)
This study aims to determine the effect of Dhikr Al-Ma'tsurat therapy on mothers who experience Parenting Stress while accompanying their children in Distance Learning (PJJ). The participants of the study were mothers who found 32 people who were obtained by purposive sampling technique. The implementation method applied is a quasi-experimental method with a research model using one group pre-test and post-test. The measuring instrument used is the Gratitude Scale (20 items, = 0.830), and the Parental Stress Scale, (18 items, = 0.855). Participants were given an intervention, namely providing material about the importance of offline dhikr, and reading Al-Ma'tsurat dhikr for 7 consecutive days, morning and evening. The results of the analysis carried out using the non-parametric test (Wilcoxon) Statistical Package for the Social Sciences (SPSS) version 22 on the Gratitude variable, the Asymp value. Signature. (2-tails) = 0.164. In the Parenting Stress variable, the Asymp value. Signature. (2-tails) = 0.309. Can Key that Asymp. Signature. (2-tailed) > 0.05, so there is no significant difference between the pre-test and post-test scores on the Gratitude variable and Parenting Stress variable. Suggestions for further researchers to pay attention to research subjects specifically.